The use of heat recovery devices for reducing energy consumption of treating ventilation air in a tropical operating theatre - Yau, Y.H.; Lim, C.B. (2009)
In the operating theatre, where exhausted air is not permitted to be re-circulated, maintaining the conditions could be tedious on the HVAC systems and found to be energy inefficient. This research will look into the potential energy savings using heat recovery devices in treating the ventilation air, without compromising the occupants’ thermal comfort and health in the conditioned space. For the purpose of this research, Operating Theatre 1 of a private hospital in Malaysia was used for analysis and simulation. The existing air conditioning system was modeled in TRNSYS as the baseline model and verified using measured data obtained from the fieldwork. Two heat recovery devices were used in the two- redesign systems and simulated in TRNSYS to analyse the energy saving potential of these devices. The results indicated that the heat recovery wheel could reduce the annual operating cost by 31% while the heat pipe heat exchanger by 28%.